Aplikasi Pengelolaan Stok Bahan Baku dengan Metode Waterfall Pada Pabrik Plastik - Lee, Francka Sakti; Aprilia, Keysia; Dinata, David Freggy; Fernando, William; Andry, Johanes Fernandes (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
All business sectors currently including small, medium and large businesses, are taking full advantage of the use of technology. Plastic factory is a factory that processes plastic ore raw materials into various plastic products. The problem is, the arrangements for procuring raw materials and recording stock of goods are still not computerized. As a result, the availability of raw goods is often not on time and lacks quality. Raw material stock management has not been integrated into the system, so production process delays or raw material waste often occur due to inaccurate calculations, resulting in large losses. Reporting is also hampered because manual data reconciliation takes longer and involves a lot of human error. This research aims to develop a desktop-based inventory application using the Waterfall method which consists of five phases, namely Communication, Planning, Modeling, Construction and Deployment. The result of this research is a web-based inventory application that can carry out integrated data recording, and faster reporting processes. Thus, the design of this inventory application can help all parties in managing stock and inventory data in warehouse.